Pemaknaan Akuntabilitas Dana Desa: Studi Fenomenologi atas Praktik, Persepsi, dan Hambatan Pengelolaan Dana Desa di Lembang Ma’kuan Pare, Kecamatan Rantebua, Kabupaten Toraja Utara - Westerini Lusdani; Yohanis Lotong Ta’dung; Chrismesi Pagiu; Rati Pundissing (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
This study aims to explore the meaning of Village Fund accountability in Lembang Ma’kuan Pare, Rantebua District, North Toraja Regency. Utilizing a qualitative approach with a hermeneutic phenomenological design, data were gathered through in-depth interviews, observation, and documentation involving lembang officials, customary leaders, and local communities. The results reveal a conflict of dual systems in practice. Vertically, accountability is trapped in pseudo-formalism merely to satisfy administrative compliance within the SISKEUDES digital application. Conversely, horizontally, the authentic meaning of accountability thrives through cosmo-social moral obligations embedded in the "Tongkonan" customary order and the "Sipangkari" deliberation tradition. The fear of losing family honor ("longko’") in the eyes of custom serves as a social control instrument that is far more revered and feared by village officials than state administrative penalties. Nevertheless, the effectiveness of governance is still hindered by structural constraints, such as the digital literacy divide and limited internet connectivity, which intertwine with paternalistic cultural barriers that restrict the critical capacity of ordinary citizens. This study recommends adaptive policy reforms that harmonize digital standardization with local customary institutions to achieve emancipatory village accountability.